Multidrug-Resistant Escherichia albertii: Co-occurrence of β-Lactamase and MCR-1 Encoding Genes - Li, Qun; Wang, Hong; Xu, Yanmei; Bai, Xiangning; Wang, Jianping; Zhang, Zhengdong; Liu, Xiang; Miao, Yimao; Zhang, Ling; Li, Xinqiong; Zou, Nianli; Yan, Guodong; et al. (Frontiers in Microbiology, 2018)
Escherichia albertii is an emerging member of the Enterobacteriaceae causing human and animal enteric infections. Antimicrobial resistance among enteropathogens has been reported to be increasing in the past years. The purpose of this study was to investigate antibiotic resistance and resistance genes in E. albertii isolated from Zigong city, Sichuan province, China. The susceptibility to 21 antimicrobial agents was determined by Kirby-Bauer disk diffusion method. The highest prevalence was tetracycline resistance with a rate of 62.7%, followed by resistance to nalidixic acid and streptomycin with a rate of 56.9% and 51.0%, respectively. All isolates were sensitive or intermediate susceptible to imipenem, meropenem, amoxicillin–clavulanic acid and levofloxacin. Among 51 E. albertii isolates, 15 were ESBL-producing as confirmed by the double disk test. The main β-lactamase gene groups, i.e. blaTEM, blaSHV, and blaCTX-M, were detected in17, 20 and 22 isolates, respectively. Furthermore, four colistin-resistant isolates with minimum inhibitory concentrations (MICs) of 8 mg/L were identified. The colistin-resistant isolates all harbored mcr-1 and blaCTX-M-55, Genome sequencing showed that E. albertii strain SP140150 carried mcr-1 and blaCTX-M-55 in two different plasmids. This study provided significant information regarding antibiotic resistance profiles and identified the co-occurrence of β-lactamase and MCR-1 encoding genes in E. albertii isolates.